The use of willingness-to-pay (WTP) method to identify potential for use of solar energy - Abdol Mulok, Norleen Fariza (2008)
Solar energy is one of the renewable energy systems that are the most environmentally friendly means of providing electricity. Developing countries such as in Asia has experiencing spectacular economic growth over the past two decades. Improvement in living standards increases the demand for electronic appliances and others for living comfort. This will result in the pressure of energy demand. One of the ways to improve the energy efficiency is by the use of clean energy such as solar energy as a real solution. Presently, the common issue in developing Asian countries is subsidies for fossil fuels which have been the obstacle to the penetration of renewable energy. As for this study, Kuala Lumpur has been chosen as the study area. This study focused on the awareness of the public on the solar energy and their willingness to pay (WTP) and use through observation and survey. For this study, one hundred and twenty respondents were involved. Result shows that the level of awareness is high (83%). Result shows 26.2% WTP of RM 5,000; with a mode value of RM 4,140. A linear correlation exists between marital status and family income on how much people are willing to spend. Higher family income and single respondents tend to have higher WTP. However, overall interest on solar energy depends on income and gender. Those with higher personal income are more interested in this technology. It also shows that female have higher interest in solar energy.